2016
DOI: 10.1177/0748233715598267
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells-conditioned medium protects PC12 cells against 2,5-hexanedione-induced apoptosis via inhibiting mitochondria-dependent caspase 3 pathway

Abstract: Studies suggested that the conditioned medium of mesenchymal stem cells (MSC-CM) inhibited the increased apoptosis in various cells. However, there are no reports underlying the protection of MSC-CM against 2,5-hexanedione (HD)-induced apoptosis in neural cells. In the present study, the viability was observed in PC12 cells that received HD alone or with MSC-CM by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. Apoptosis was estimated by Hoechst 33342 staining and flow cytometry. Mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The disruption of this process is associated with a wide variety of neurodegenerative diseases, including HD-induced neuropathy 25 . Previously, we reported the protective effect of BMSC-CM against HD-induced apoptosis in PC12 cells, which was associated with reduction of Bax expression, Cyt C release and caspase-3 activity 9 . In this study, we delve deeper into investigating the anti-apoptotic and neuroprotective efficacy of BMSC in HD-intoxicated rats.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The disruption of this process is associated with a wide variety of neurodegenerative diseases, including HD-induced neuropathy 25 . Previously, we reported the protective effect of BMSC-CM against HD-induced apoptosis in PC12 cells, which was associated with reduction of Bax expression, Cyt C release and caspase-3 activity 9 . In this study, we delve deeper into investigating the anti-apoptotic and neuroprotective efficacy of BMSC in HD-intoxicated rats.…”
Section: Discussionmentioning
confidence: 82%
“…To further demonstrate the role of NGF in BMSC-afforded neuroprotection, we tested the impact of NGF neutralization on the anti-apoptotic effect of BMSC in an in vitro model of HD-induced apoptosis. We recently demonstrated that NGF released by BMSC accumulates in BMSC-CM and is capable of protecting PC12 cells against HD-induced apoptosis 9 . Consistent with previous report, the protective effect of BMSC-CM against HD-induced apoptosis was also observed in ventral spinal cord 4.1 (VSC4.1) cells, a cell line of dorsal motor neurons, by showing decreased number of TUNEL-positive cells and activity of caspase-3 compared with HD alone group ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we extended the therapeutic efficacy of BMSC into the neuropathy induced by occupational or environmental neurotoxicants, such as n -hexane. The potent protective effects displayed by conditioned medium prepared from BMSC (BMSC-CM) against HD-induced apoptosis were observed in PC12 cells, which was a rat pheochromocytoma cell line and possessed properties of neurons 9 . BMSC transplantation also attenuated HD-induced neuronal damage and improved the motor performance in rats 10 .…”
Section: Introductionmentioning
confidence: 99%